Histoid leprosy mimicking lichen planus - Kimberly, Kesya; Alviariza, Annisa; Ferina, Siti Aisha Nabila; Esti, Prima Kartika; Peranginangin, Lenti Br.; Komarasari, Eka (Journal of General - Procedural Dermatology and Venereology Indonesia, 2023)
Background: Histoid leprosy is a rare variant of lepromatous leprosy (LL), characterized by unique clinical, histopathological, and microbiological features. This type of leprosy is caused by multidrug therapy (MDT) drug resistance, train mutation of Mycobacterium leprae, or genetic factors. Case Illustration: A 21-year-old Indonesian woman with a family history of histoid leprosy complained of multiple hypo-esthetic erythematous partly flat-topped papules around the lesion on the face and bilateral superior and inferior extremities for the last two years. A Slit-skin smear examination revealed acid-fast bacilli with a bacterial index (BI) of 4.17+ and morphological index (MI) of 1%. Histopathological examination on hematoxylin & eosin (H&E) stained revealed epidermal atrophy, Grenz zone, and bundles of thin spindle-like histiocytes with Virchow cells. Ziehl-Nielsen stain showed copious acid-fast bacilli. Therefore, the diagnosis of histoid leprosy was established. Discussion: Lichen planus (LP) was considered because LP typically presents as pruritic, polygonal, violaceous flat-topped papules with symmetric distribution on the flexural surfaces of the forearms, wrists, and ankles, as well as the dorsal surface of the hands and shins. However, the face is rarely affected in LP. The patient’s slit-skin smear and histopathological examinations presented strong evidence for histoid leprosy. Treatment with an MDT regimen resulted in clinical improvements as the erythematous lesions transformed into hyperpigmentation after weeks of treatment. Conclusion: Histoid leprosy mimicking LP lesions in this patient developed without any prior administration of agents. Additionally, the patient had a high bacillary load, indicating a potential reservoir of the infection as the patient had a family history of leprosy.